2021
DOI: 10.1152/ajpendo.00008.2021
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and estrogen: common pathways in Alzheimer's disease pathology

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease that is characterized by progressive declines in cognitive function. Current epidemiological data indicates significant sex-linked disparities, where females have a higher risk of developing AD compared to male counterparts. This disparity necessitates further investigations to uncover the pathological and molecular factors influencing these sex differences. Although the underlying pathways behind this observed disparity remain elusive, recent research po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Both the reduction in sABPPα fragments and the increase in BACE1 activity are commonly associated with increased levels of AB peptides and subsequent plaques in patients with AD ( 15 , 25 , 48 ). Although we were unable to directly measure AB peptide content in our study, BACE1 is the rate-limiting enzymatic step involved with the amyloidogenic cascade and studies have demonstrated increases in AB peptide content following higher activity levels of BACE1 ( 3 , 12 , 15 , 43 , 49 ). Work from our lab has previously shown that BACE1 activity is lowered with exercise in male mice potentially explaining these compensatory effects we saw in the OVX VWR group ( 15 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Both the reduction in sABPPα fragments and the increase in BACE1 activity are commonly associated with increased levels of AB peptides and subsequent plaques in patients with AD ( 15 , 25 , 48 ). Although we were unable to directly measure AB peptide content in our study, BACE1 is the rate-limiting enzymatic step involved with the amyloidogenic cascade and studies have demonstrated increases in AB peptide content following higher activity levels of BACE1 ( 3 , 12 , 15 , 43 , 49 ). Work from our lab has previously shown that BACE1 activity is lowered with exercise in male mice potentially explaining these compensatory effects we saw in the OVX VWR group ( 15 ).…”
Section: Discussionmentioning
confidence: 89%
“…Initially, it was thought that this was due to the longer lifespan of females, however, even after accounting for age, the difference between males and females is present ( 8 ). It is possible that this discrepancy is caused by the estrogen depletion that females experience during menopause ( 8 12 ). Estrogen is the most abundant ovarian hormone and is a regulator of brain-derived neurotrophic factor (BDNF), a protein that maintains neuronal plasticity and health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Aβ-dependent pathways play a key role in AD pathogenesis, Aβ-independent pathways are also known to be important [12,13]. The association between the endocrine system and AD pathogenesis has recently garnered attention [38,39]. The ndings collectively suggest that the health risks of HTPs via Aβ-independent pathways, such as those in the endocrine system, in AD pathogenesis are worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and satellite cell function are also estrogen sensitive and can contribute to muscle strength preservation [ 134 , 135 ]. Estrogen plays a crucial role in the processing of amyloid precursor protein (APP) and general neuronal health, which is partially via the modulation of brain-derived neurotrophic factor (BDNF), a factor that is similarly decreased in postmenopausal women and negatively associated with AD progression [ 128 , 129 ].…”
Section: Estrogen Signalingmentioning
confidence: 99%